MiR-223-3p regulates erythropoiesis by targeting TGFBR3/Smad signaling pathway in hemoglobin H-Constant Spring disease - Lan Lan; Xinyu Wang; Simeng Zhang; Dan Zeng; Limin Mo; Qiao Feng; Jun Li; Chunjiang Zhu (Annals of Medicine)
Background MicroRNAs (miRNAs) have emerged as regulators of pathogenesis in hematopoiesis by targeting post-transcription mRNA regulation. However, the involvement of miRNAs in hemoglobin H-Constant Spring (HbH-CS) disease remains unclear. The present study analyzed miRNAs differential expression profile between patients with HbH-CS disease and healthy subjects by Arraystar Human small RNA Microarray.Methods The differential expression profiles of miRNAs between HbH-CS patients and healthy individuals were analyzed using Arraystar human small RNA microarrays. Quantitative real-time PCR and Western blot were used to detect the mRNA and protein expression. Bioinformatics methods were used to predict the target genes of miRNAs, and the regulatory relationship between miRNAs and target genes was verified by dual-luciferase reporter assay. Cell apoptosis was detected by flow cytometry, and cell proliferative capacity was detected by CC K-8 assay.Results MiR-223-3p was significantly down-regulated in HbH-CS patients. Dual-luciferase reporter assay demonstrated that miR-223-3p specifically targeted TGFBR3. The in vitro experiments showed that miR-223-3p inversely regulated the expression levels of TGFBR3, Smad2/3, and P-Smad2. We found that overexpression of miR-223-3p in K562 cells significantly promoted cellular proliferation and inhibited cellular apoptosis by suppressing expression of TGFBR3, Smad2/3, and P-Smad2. Moreover, up-regulation of miR-223-3p in induced K562 cells increased the expression levels of hemoglobin and mean corpuscular hemoglobin.Conclusion In conclusion, this study indicated that the interaction between miR-223-3p and TGFBR3/Smad signaling pathway might affect erythropoiesis in HbH-CS disease, which can provide more information for the treatment of patients.